Sensitivity analysis of the dependence of the Carbon Bond Mechanism IV (CBM-IV) on the initial air composition under an urban condition. (15th October 2019) - Cao, Le; Gao, Mengmeng; Li, Simeng; Yi, Ziwei; Meng, Xianhong
Abstract: CBM-IV mechanism is one of the most-commonly used atmospheric reaction mechanisms in the model studies of air pollution. In this study, by using a concentration sensitivity analysis, we investigated the dependence of NO, NO 2 and O 3 on the initial air composition in the CBM-IV mechanism under a typical urban condition. The initial values of the components that are identified important in the sensitivity analysis were also modified to see the relevant changes in the reaction system. The results show that at the beginning of the simulation, NO, NO 2 and O 3 are mostly affected by the titration reaction. During this period, the NO mixing ratio depends negatively on the initial O 3 and positively on the initial nitrogen oxides. Moreover, the NO 2 mixing ratio was found positively correlated with the initial NO, while its dependence on the initial O 3 transits between positive and negative. In contrast to that, O 3 at this stage has the strongest positive dependence on its own initial concentration, but a negative association with the initial NO . However, as the reaction proceeds, the dependence of O 3 and the nitrogen oxides on the initial air composition changes. During the end of the simulation, the change of NO and NO 2 was found moderately associated with their initial values, but the influence caused by the modification of the initial O 3 is negligible. Similarly, ozone at this time was also found less impacted by its initial value. Instead, the ozone level under equilibrium relies mostly on the initial NO and NO 2 . Highlights: The dependence of CBM-IV on the initial air composition is investigated. At the early stage, NOx and ozone are determined by the titration reaction. The dependence of the final ozone level on the initial value of ozone is weak.